Bone. 8, Treasure hunters - Smith, Jeff, 1960 February 27- (Smith, Jeff, 1960 February 27- Bone, 2008)
A graphic novel which presents the story of the Bone cousins who try to save ancient Atheia from The Hooded One but the time is short, and they must hurry before the city is totally destroyed.